MINIMISING RISK OF TRAIN DERAILMENT AND ITS SIGNIFICANT CONSEQUENCES IN INDONESIA - , DANANG SULISTYAWAN, Dr. Eng. Imam Muthohar, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Train derailment is a big problem on Indonesian railways. According to the Indonesian Ministry of Transportation (MoT), there were 531 occurrences of train derailments during the period 2004-2010. It represents approximately 75% of all train accidents which occurred in Indonesia in that period. Furthermore, the MoT recorded that approximately half (260) of the train derailments involved passenger trains. The main impacts of Indonesian passenger train derailments during the 2004-2010 periods were passenger injuries and death, railway service disruption, and material (track and rolling stock) losses. By analysing the train derailment investigation reports published by the KNKT and the summary of train derailment data published by the MoT, it was found the passenger train derailments were caused by some significant factors which were related to four main issues: rolling stock, infrastructure, switch and crossings, and operational issues. Furthermore, 8 serious passenger train derailments reported by the KNKT imply that casualties may be related to the condition of the derailed trains. Using information in the literature, a study was conducted to assess possible initial problems and causal factors of some significant factors which have caused passenger train derailments in Indonesia. An assessment was then made of the various approaches available within the railway industry to reduce the risk of train derailments by addressing the underlying causes. Based on that study, five recommendations are proposed to minimise risk of passenger train derailments and its consequences in Indonesian railways: examination and monitoring programmes, maintenances and evaluation procedures, replacement and renewal programmes, installation and modification programmes, and recording and audit.